Knowledge internalization as a measure of results for organizational knowledge transfer: proposition of a theoretical framework - Helen Aquino; José Márcio de Castro (Tourism & Management Studies)
As this is result of the transfer of knowledge, most studies on this subject have considered the implementation of organizational knowledge as a positive result and as the end of the transfer process; internalization as active adoption of knowledge has seldom been investigated. This is assuming that it is only when knowledge is internalized by the recipient company that the transfer process really becomes effective and incorporated into organizational routine. The aim of this paper is propose a theoretical framework using internalization as the variable to analyze the effectiveness of the knowledge transfer process. For this, a comprehensive literature review was conducted that resulted in the identification of important variables that moderate the internalization: the disseminative capacity and the absorptive capacity. Moreover, this article proposes an analysis of internalization from a multidimensional perspective, considering the appropriation of knowledge and time taken to internalize as extension factors of knowledge internalization.